Cartography and Nation in Latin America (19th and 20th centuries): an approach to the cases of Argentina, Mexico and Colombia (2019)
This article aims to approximate the way in which geography and history have addressed the relationship between cartographic production and nation-state formation in Argentina, Mexico and Colombia during the 19th century and part of the 20th century. Through a review by some authors on the subject, it is intended to show the existence of a transformation in the way of addressing the history of cartography in Latin America. This change is manifested in the fact of considering the map as something that not only refers to the state of the art in a specific period, linking it to the world of representation and power relations, as a key instrument in the geopolitical consolidation of Latin American national states. It also seeks to demonstrate some common lines of work, as well as identify specific issues by country.